Morphological study of Ionic Exchange Resins to support the 14C release investigation from radioactive wastes—EURATOM CAST project. Issue 6 (28th January 2019) - Rizzo, A; Bruni, S; Gessi, A; Marghella, G; Moretti, L; Telloli, C; Rizzato, C; Luce, A
ABSTRACT: Radiocarbon ( 14 C) is one of the key radionuclides for the performance and safety assessment of a radioactive waste disposal, due to its high activity concentration in waste materials from the nuclear cycle and to its mobility. The measurement of the 14 C content in spent ion exchange resins from nuclear reactors is important for the safety assessment of the disposal concept and for the choice of the appropriate treatment/disposal method. Ion exchange resins are commonly used in nuclear reactors as filters for the purification of process liquids or wastes streams and they retain molecules containing radioactive isotopes, among which is 14 C. Their efficiency, both as filters and as waste containers, is strictly connected with the morphology. The preservation of spherical shape upon aging is one of the key parameters for their quality assessment and for the evaluation of the potential release of 14 C during storage conditions. In this study, the change in IERs morphology during storage periods has been investigated in order to verify correlation with 14 C release. Both brand new and aged specimens have been studied in order to assess the quality of the resins after 10 yr of storage and to contribute to the understanding of 14 C release mechanisms.